2021
DOI: 10.3390/md19100542
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Chondroprotective Food Supplements Based on Collagen Hydrolysate and Compounds Isolated from Marine Organisms

Abstract: Osteoarthritis belongs to the most common joint diseases in humans and animals and shows increased incidence in older patients. The bioactivities of collagen hydrolysates, sulfated glucosamine and a special fatty acid enriched dog-food were tested in a dog patient study of 52 dogs as potential therapeutic treatment options in early osteoarthritis. Biophysical, biochemical, cell biological and molecular modeling methods support that these well-defined substances may act as effective nutraceuticals. Importantly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…The emulsion is a thermodynamically unstable system, which mainly has problems with physical instability. , Thus, improving emulsion physical stability against gravitational separation and droplet aggregation has attracted much more interest. Beside health benefits in food administration, our results also provide important insights when peptide- and protein-based drugs have to be encapsulated for an oral use in a clinical context. …”
Section: Discussionmentioning
confidence: 94%
“…The emulsion is a thermodynamically unstable system, which mainly has problems with physical instability. , Thus, improving emulsion physical stability against gravitational separation and droplet aggregation has attracted much more interest. Beside health benefits in food administration, our results also provide important insights when peptide- and protein-based drugs have to be encapsulated for an oral use in a clinical context. …”
Section: Discussionmentioning
confidence: 94%
“…ADAM (A Disintegrin And metalloprotease) 12 has also been implicated in the development of pathogen various forms of cancer, hypertension, liver fibrogenesis, and asthma ( Estrella et al, 2009 ). Since collagen–integrin ( Siebert et al, 2010 ) and collagen–ADAM interactions ( Eckert et al, 2021 ) play a dominant role in cell experiments ( Petridis et al, 2011 ; Martinez-Olivera et al, 2018 ) where Mg 2+ is replaced by Co 2+ we have already discussed their feasibility here.…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis shows that bond cleavage of axial and equatorial ligands can vary within a few kcal/mol in binding energy. The quantum chemical DFT data may contribute to a better understanding of the function relationship of integrin ligand complexes including the role of integrins in tissue repair, glycobiology and neurooncology ( Racine-Samson et al, 1997 ; Gabius et al, 2004 ; André et al, 2005 ; Bhunia et al, 2010 ; Petridis et al, 2011 ; Stötzel et al, 2012 ; Tsvetkov et al, 2012 ; Kanakis et al, 2013 ; Glinskii et al, 2014 ; Hussein et al, 2015 ; Zhang et al, 2016a ; Cornelissen and Van Vliet, 2016 ; Malric et al, 2017 ; Marsico et al, 2018 ; Martinez-Olivera et al, 2018 ; McCarthy et al, 2018 ; Sharma et al, 2020 ; Eckert et al, 2021 ). The polysialylated neural cell adhesion molecule (NCAM) as well as the sulfated HNK-1 epitope are together with β1-integrin involved in cell differentiation processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen hydrolysates have been effectively utilized due to their good moisturizing properties at the stratum corneum layer of the skin, which reduce the effects of skin dryness, laxity and wrinkles [45]. Eckert et al (2021) reported that collagen hydrolysates of fish, jellyfish and bovine origin that were used as food supplements could maintain cartilage health of dogs and could be as potential therapeutic drugs in early osteoarthritis [46]. Schadow et al (2017) used several collagen hydrolysates as nutraceuticals for human osteoarthritis, and found that there were marked differences between collagen hydrolysates of different origins [47].…”
Section: Discussionmentioning
confidence: 99%